Female sex is strongly associated with cognitive impairment in HIV infection - Duarte, Eric Andrius Coelho; Benevides, Maria Luiza; Martins, André Luiz Pereira; Duarte, Edson Pillotto; Weller, Ana Beatriz Santandrea; de Azevedo, Laura Oliveira Coutinho; de Oliveira Thaís, Maria Emília Rodrigues; Nunes, Jean Costa (Neurological sciences, 2021)
Background Neurocognitive disorders remain frequent despite highly active antiretroviral treatment (HAART). The CNS is known as the sanctuary of HIV infection, where persistent neuroinflammation occurs regardless of viral suppression. Moreover, opportunistic infections, neurovascular damage and HAART neurotoxicity contribute to neurocognitive impairment. Therefore, detailed epidemiological studies might help to elucidate those complex mechanisms. Objective To investigate the prevalence of cognitive impairment and the associated sociodemographic, clinical and neuropsychological variables among HIV-infected patients admitted to a tertiary centre, in southern Brazil. Methods An observational, cross-sectional and analytic study was conducted between February 2019 and March 2020, in Hospital Nereu Ramos (HNR), with148 HIV-infected patients. They were interviewed, submitted to the International HIV Dementia Scale (IHDS) and had their medical data analysed. Results The prevalence of cognitive impairment was 69.6%. It was higher among women (OR = 3.5; 95% CI 1.5-8; p < 0.01), independently of depression, educational status and age. Full years of schooling were strongly associated with IHDS scores ( p < 0.01). Patient Health Questionnaire-9 (PHQ-9) scores for depression ( p = 0.8), time since HIV diagnosis ( p = 0.2), CD4 + cell counts ( p = 0.8) and viral load ( p = 0.8) were not associated with IHDS scale. Conclusion A high prevalence of cognitive impairment in HIV-infected patients was identified, independently associated with the female sex and fewer years of schooling. Further studies are needed to clarify the differences in the pathophysiology between sexes and the role of cognitive reserve in prevention of cognitive impairment in HIV infection.